Pemaknaan Branding Hijab dalam Studi Semiotika Iklan XYZ di Kanal YouTube X Indonesia - Fatimatuz Zahroh; Reni Shinta Dewi (Pusat Riset dan Inovasi Nasional, 2024)
Women wearing hijab are currently the main target of the hijab fashion industry, along with the increasing popularity of the hijaber community that is growing both online through social media and offline. The hijab, which initially only functioned as a head covering, has now undergone a transformation into a part of a fashion trend that is loaded with aesthetic, style, and identity values. In this context, the Shampoo X Hijab Ice Tea advertisement offers a space for hijab-wearing women to express their existence through constructed imagery. This study aims to uncover the meanings contained in the advertisement by using a qualitative descriptive approach and Roland Barthes semiotic analysis method. This approach was chosen because it is able to unravel the signs, symbols, and myths hidden behind the representation of advertising, as well as understand the ideological dimensions that are not explicitly visible. Data collection is carried out through visual documentation and detailed observation of each ad scene aired on the Youtube platform. The results of the study show that even though this advertisement is commercial, there is a construction of meaning that displays the image of women wearing hijab as modern figures who are confident, healthy, productive, and still maintain freshness throughout the day. In addition, the advertisement depicts hijab-wearing women who are actively learning, maintaining a graceful, empowered appearance, and representing modern Muslim women who are harmonious between religious identity and contemporary lifestyles. In conclusion, the Shampoo X Hijab Ice Tea advertisement not only sells products, but also builds myths about modern Muslim women who are empowered, elegant, and confident. Semiotic analysis opens up opportunities to understand that advertising is not just a promotional medium, but also an important means in the formation of images, identities, ideologies, and social perceptions in society.